A study of food insecurity and rural development in the Gambia: the impact of rural weekly markets (Lumos) - Sanneh Patrick, Sarjo (Kansas State University, 2009)
Food insecurity poses an enormous challenge and is a matter of extreme urgency for The Gambia, where more than half of the population lives below the poverty line. Although extensive research confirms the problems of food insecurity in Africa, no research has concurrently advanced a bottom-up and top-down neo-endogenous theoretical framework to explore 1) the dynamics of food insecurity in The Gambia and 2) the extent to which measures used to combat it have had a positive impact. The current research aims to fill this gap by employing concurrent triangulation (mixed) methods that incorporate primary and secondary data sources. As envisaged by the neo-endogenous approach, structured interviews with participants in the weekly rural markets/ Lumo(s), underscore the crucial role this indigenous marketing system plays. This marketing system embeds socioeconomic activities in rural territories through the utilization of social and cultural capital that reduce transaction costs involved in direct marketing. Consequently this initiative increases Wassu community’s access to food and stabilizes the food supply. The results also reveal moderate effects of various interventions, particularly in the Western and North Bank divisions, where agricultural production of various crops and livestock has improved the livelihood of those rural communities. At the local level, the allocation of a greater proportion of arable land to coarse grain production along with the decline in peanut production hold great promise for reducing the problem of food insecurity. Although food insecurity still prevails in much of rural Gambia as indicated by the scale of stunting among children under age five, measures are being taken to address the problem. Combined with intervention projects and other developmental effects, the potential for the Lumo(s) to reverse food insecurity in the country is great, contingent upon the central government and international lending agencies’ devolution of significant powers and transfer of funds directly to rural territories.
Keywords: Food insecurity in The Gambia; Rural weekly markets (Lomos) in The Gambia; Rural development in The Gambia; Neo-endogenous approach; Embeddedness; Rural poverty and hunger in Africa; Sociology, General (0626)